Analysis of lithuanian transport sector possibilities in the context of european‐asian trade relations - Vasiliauskas, Aidas V.; Barysienė, Jurgita (Transport, 2008)
The fundamental importance of an integrated international multimodal transport system has been clearly recognised. The identification and development of well functioning transport relations on the basis of existing transport corridors and networks requires properly defined, formalised, and coordinated joint actions among the relevant countries, international institutions and organisations. The geographical position of Lithuania has determined that the country is crossed by the two European transport corridors approved at the Conferences of the European Transport Ministers in Crete and Helsinki, creating ability for Lithuania in trade between EU and Asia. Paper presents an overview of recent changes in world economy and international trade emphasizing the growing importance of European ‐ Asian relations. Then analysis of existing transport links assuring possible ways for freight movements between these two regions are examined and method for the comparison of transportation alternatives based on corridor utility is presented. Finally, some key development trends towards the strengthening of Lithuanian transport system role in the context of European‐Asian trade relations are discussed. First published online: 27 Oct 2010